Davener's Dermatosis in Children: An Underrecognized Entity - Kotturningappar C. Shashidhar; Sahana M. Srinivas (Wolters Kluwer Medknow Publications, 2024)
Davener's dermatosis is a variant of frictional hypermelanosis characterized by midline hyperpigmented patches with indistinct borders, typically distributed along the skin overlying the bony protuberances of the lower thoracolumbar spine. Hereby, we report two children aged 10 and 12 years who presented with hyperpigmented skin lesions on the lower back. Both children had a history of exposure to prolonged friction at the affected site. The clinical diagnosis of Davener's dermatosis was made, supported by dermoscopic findings. The parents were educated regarding the benign nature of the condition and the required changes to be made in postural habits and avoidance of friction.